Characterizing disability at the Iganga-Mayuge Demographic Surveillance System (IM-DSS), Uganda. Issue 13 (18th June 2016) - Bachani, Abdulgafoor M.; Galiwango, Edward; Kadobera, Daniel; Bentley, Jacob A.; Bishai, David; Wegener, Stephen; Zia, Nukhba; Hyder, Adnan A.
Abstract: Purpose : There is a need to better measure disability as an outcome to understand the magnitude of the problem and its impact on health and socio-economic status. The aim of this study was to characterize the physical disabilities present at the Iganga-Mayuge Demographic Surveillance Site (IM-DSS) in Uganda. Methods : WHODAS 2.0 was used to examine the consequences of disability on activity limitations and participation in society. One thousand five hundred and fourteen individuals over the age of 18 at the IM-DSS with previously identified physical disabilities were included. Total and domain scores were calculated, and regression analyses examined differences by age, sex, education, occupation and SES. Results: The mean total score was 40.72. Domain 2 – getting around, had the highest mean score (57.21), followed by household activities (55.18). Domains 5.2 (work/school activities) and 6 (participation in society) also had relatively high mean scores – 47.71 and 49.44, respectively. Conclusion : This study serves as an indication of what the major limitations are among individuals in rural Uganda with physical disabilities. In general, individuals with disabilities had the most trouble on getting around, life activities and participation in society. This can guide public health planners and policy-makers on priorities to ameliorate the impact of disabilities in this population. Implications for Rehabilitation: This study found that in general, individuals with disabilities had the most trouble on getting around, life activities and participation in society. This can guide public health planners and policy-makers on rehabilitation priorities to ameliorate the impact of disabilities in this population. Efforts can be made to develop and implement rehabilitation programs that cater to the needs of vulnerable populations including females and older individuals. Programs that focus on education and employment for physically disabled individuals ought to be given priority. These could include legislative changes, and modification of the physical environment, among others.